MARKETING AND BUSINESS DEVELOPMENT CAPABILITIES IN NURSE ENTREPRENEURSHIP: A SCOPUS-BASED SYSTEMATIC LITERATURE REVIEW - Shapely Ambalao; Grace Fresania Kaparang; Michelle Sambuaga (Smart Education, 2026)
Abstract: Nurse entrepreneurship has long been discussed as a response to healthcare service gaps, professional autonomy, and new forms of care delivery. However, the evidence remains fragmented across practice reports, historical accounts, qualitative studies, and educational reviews, while market-facing and business-development capabilities are rarely synthesized as an integrated construct. This review maps the development of Scopus-indexed nurse entrepreneurship research and synthesizes the marketing and business development capabilities associated with venture creation, legitimacy, commercialization, and sustainability. A Scopus-based systematic literature review was reported using PRISMA 2020 and informed by SPAR-4-SLR. Inclusion criteria were English language, nursing context, and article document type. Twenty-two articles published from 1985 to 2025 were included in bibliometric analysis; 17 records with usable abstracts supported thematic coding. Keyword co-occurrence was examined using full counting and a minimum occurrence threshold of two. Six empirical or review reports were provisionally appraised using design-appropriate JBI tools. The corpus received 116 Scopus citations and was distributed across 18 sources. Healthcare marketing (18 occurrences; total link strength [TLS] = 103), nursing services (15; TLS = 80), entrepreneurship (14; TLS = 77), professional practice (13; TLS = 69), and financial management (12; TLS = 61) formed the conceptual core. Network analysis produced two broad clusters: a market-operational cluster and an entrepreneurial-professional-development cluster. Overlay visualization indicated a transition from private practice, financial management, and service promotion toward leadership, professional competence, communication, and sustainable value. Five capability domains were synthesized: market sensing and opportunity recognition; marketing communication, positioning, and trust; business planning and financial management; networking, partnerships, and referrals; and service innovation and commercialization. Nurse entrepreneurship research recognizes many practical business activities but has not yet developed a cumulative, theory-driven capability model. Future research should measure capability configurations and link them to patient trust, service adoption, financial viability, growth, and social value. Keywords: business development; entrepreneurial nursing; nurse entrepreneurship; marketing capabilities Abstrak: Kewirausahaan perawat telah lama dibahas sebagai respons terhadap kesenjangan layanan kesehatan, otonomi profesional, dan bentuk-bentuk baru pemberian layanan kesehatan. Namun, bukti-bukti yang ada masih tersebar dalam laporan praktik, catatan sejarah, studi kualitatif, dan tinjauan pendidikan, sementara kemampuan yang berorientasi pada pasar dan pengembangan bisnis jarang disintesis sebagai sebuah konstruk yang terintegrasi. Tinjauan ini memetakan perkembangan penelitian kewirausahaan perawat yang terindeks Scopus serta menyintesis kemampuan pemasaran dan pengembangan bisnis yang terkait dengan pembentukan usaha, legitimasi, komersialisasi, dan keberlanjutan. Tinjauan pustaka sistematis berbasis Scopus ini dilaporkan menggunakan pedoman PRISMA 2020 dan kerangka SPAR-4-SLR. Kriteria inklusi mencakup penggunaan bahasa Inggris, konteks keperawatan, dan jenis dokumen artikel. Sebanyak dua puluh dua artikel yang diterbitkan antara tahun 1985 hingga 2025 disertakan dalam analisis bibliometrik; 17 rekaman dengan abstrak yang dapat digunakan mendukung proses pengodean tematik. Ko-okurensi kata kunci diperiksa menggunakan metode full counting dengan ambang batas kemunculan minimal dua kali. Enam laporan empiris atau tinjauan dinilai secara awal menggunakan instrumen JBI yang sesuai dengan desain penelitian. Kumpulan literatur ini memperoleh 116 sitasi Scopus dan tersebar di 18 sumber publikasi. Pemasaran layanan kesehatan (18 kemunculan; total kekuatan tautan [TLS] = 103), layanan keperawatan (15; TLS = 80), kewirausahaan (14; TLS = 77), praktik profesional (13; TLS = 69), dan manajemen keuangan (12; TLS = 61) membentuk inti konseptual. Analisis jaringan menghasilkan dua klaster besar: klaster operasional-pasar dan klaster pengembangan profesional-kewirausahaan. Visualisasi overlay menunjukkan adanya transisi dari praktik mandiri, manajemen keuangan, dan promosi layanan menuju kepemimpinan, kompetensi profesional, komunikasi, dan nilai berkelanjutan. Lima domain kemampuan disintesis: pemahaman pasar dan pengenalan peluang; komunikasi pemasaran, pemosisian, dan kepercayaan; perencanaan bisnis dan manajemen keuangan; jejaring, kemitraan, dan rujukan; serta inovasi layanan dan komersialisasi. Penelitian kewirausahaan perawat mengakui berbagai aktivitas bisnis praktis namun belum mengembangkan model kemampuan yang bersifat kumulatif dan berbasis teori. Penelitian di masa depan sebaiknya mengukur konfigurasi kemampuan dan mengaitkannya dengan kepercayaan pasien, adopsi layanan, kelayakan finansial, pertumbuhan, dan nilai sosial. Kata kunci: pengembangan bisnis; keperawatan kewirausahaan; kewirausahaan perawat; kemampuan pemasaran